Exame preventivo do câncer de colo uterino : representações sociais de profissionais do sexo de Juazeiro - BA - Sarmento, Sued Sheila (2010)
The cervical cancer is considered a public health problem in Brazil, for having an important role in morbidity and mortality among Brazilian women. The Pap test, also known as preventive test, is one of the main methods used to track changes caused by this cancer, its application being emphasized in public health programs. In view of the increasing incidence and mortality rates due to cervical cancer, despite the gradual increase in accessibility to methods in preventing this disease, one wonders about the reason for not performing this procedure on the part of the population, especially by sex workers, since these women have greater risk factors for this disease. Based on this concern, this study aimed to identify the social representations of sex workers, regarding the preventive examinations for cervical cancer. It was a study of descriptive and qualitative approach. This work was based on the idea that prevention for women in prostitution occurs through the processes they experience in their daily lives, including family and social life experiences. The way they understand and signify these processes contributes to the guidance of their health practices, among which the implementation of preventive examinations for cervical cancer. The locus of the study was Juazeiro - BA. The sample comprised 14 women and determined throughout the study. Data collection was performed using the following techniques: free association of words, imagery and semi-structured interview, applied individually, and in the same order for all participants. The collected data were analyzed using Bardin content analysis, based on the theory of Social Representations. Data analysis of free association resulted in the following answer categories: the body falling ill, feelings manifested, consequence / prevention, family, procedure and evaluation of the examination. The results of the interviews were organized into categories: 1) the examination and its importance, which was subdivided into two subcategories: a) prevention and b) diagnosis, 2) reasons which hinder adherence to the examination, which was divided into subcategories: a) inappropriate reception, b) lack of incentives / partner forbiddance, c) difficulty in coping with the examination. From the imagery technique it was found that the screening test is considered by women, mainly as an invasive procedure. The analysis of answers highlighted the importance of performing the screening test both for the prevention of diseases, and for its diagnosis, especially cervix cancer. We also observed that women perceived the exam as a situation that generates negative feelings which, most often, are related to shame, fear of pain, the possibility of positive results and lack of understanding the ritual of the examination. The sex workers of Juazeiro - BA represent the screening test as something necessary, important, permeated with unpleasant sensations, which may hinder / delay adherence to it. Much has still to be done for the health of women in its educational aspect, especially with regard to health professionals so that they are sensitized about the subjective aspects involved in cancer and procedures inherent in the prevention process.